Developmental Relationships: An Examination into the Perceptions of Students on Their Relationships with Faculty Members - Lynn Hanrahan; Timothy Hanrahan; James Concannon (Park University, 2023)
The purpose of this study was to investigate the perceptions of students on the importance of developmental relationships related to teacher satisfaction and retention. It involved the use of a 20-question survey that was focused on perceptions of on-ground undergraduate students on components of The Developmental Relationship Framework from the Search Institute. Cronbach's Alpha, T-tests, and a Mann-Whitney U test were used to analyze the data. Independent T-tests and the Mann-Whitney U Item Analysis discovered no significant differences in mean scores of survey questions and the demographic variables. While the statistical results were not significant, areas for further research were identified.